Access and rational use of medicines in the prison system in Paraíba - Karla Karolline Barreto Cardins; Claudia Helena Soares de Morais Freitas; Mônica Oliveira da Silva Simões; Gabriela Maria Cavalcanti Costa (Universidade Federal do Rio de Janeiro, 2019)
Abstract Objective: This article aims to evaluate the access and rational use of essential and strategic medicine in the prison population in Paraiba prison system. Method: Qualitative study, carried out with 13 health professionals and 43 prisoners, between February and August of 2016 in seven penitentiary units of the state of Paraiba. Results: Some interviews pointed out that the prisons have ensured the medications, others, however, have stated the constant lack of these supplies and that depend on the family to guarantee access. It has been found that those who are routinely discharged do not have the professional prescriptions and that dose monitoring is not a practice. Medications are cared for by the subjects and although storage is careful, they are kept in the cells in places with poor ventilation. Final considerations: In this way, it has been verified that, although policies guarantee the access and rational use of medicines in penitentiaries, there are cases of lack of them, besides the lack of adequate prescription, supervision of the doses taken, correct storage and follow-up to guarantee the continuity of the treatment. Implications for practice: It is perceived the need of the management to program professional capacities aimed at care in the prison system, besides identifying the gaps related to access and rational use of medicines, allowing their restructuring.